2022
DOI: 10.1186/s12905-022-01988-4
|View full text |Cite
|
Sign up to set email alerts
|

Coping with dysmenorrhea: a qualitative analysis of period pain management among students who menstruate

Abstract: Background Dysmenorrhea, or period pain, affects up to 95% of menstruating individuals and is a common cause of educational absenteeism among students who menstruate worldwide. Evidence suggests that students may lack sufficient knowledge about their menstrual health, which may impede self-management. The aim of the current study was to explore pain management strategies used by students in Ireland with painful periods and to identify their unaddressed needs across physical, psychological, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…These findings are in parallel with previous studies that found menstrual stigma restricts access to precise management advice in the home and medical sectors. 22,23 It indicates that community-wide initiatives are needed to raise knowledge of menstruation pain and its treatment. The severity of the menstrual pain of students was also the other reason preventing them from seeking healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in parallel with previous studies that found menstrual stigma restricts access to precise management advice in the home and medical sectors. 22,23 It indicates that community-wide initiatives are needed to raise knowledge of menstruation pain and its treatment. The severity of the menstrual pain of students was also the other reason preventing them from seeking healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the respondents' knowledge of dysmenorrhea was missing (56.6%), according to a prior study on the relationship between dysmenorrhea knowledge and handling in students of SMA Negeri 15 Medan, which obtained a value of p=0.000 based on the chisquare findings. It is clear from the study's findings that treatment for dysmenorrhea and knowledge of the disease is significantly correlated [3]. The better efforts made to treat dysmenorrhea in young women, the more knowledge is available regarding the disease [18]; according to findings by [8], [20], the greater teenage understanding of dysmenorrhea, the better adolescent attitude toward managing dysmenorrhea.…”
Section: Management Of Dysmenorrheamentioning
confidence: 93%
“…This complaint usually only arises 2 or 3 years after the first menstruation (menarche). Dysmenorrhea is menstruation accompanied by pain caused by spasms of the uterine muscles [2], [3]. Some women can have abnormal menstruation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, menstrual cramps are significantly affected by sociocultural attitudes, with periods being regarded as shameful in some sociocultural contexts. Additionally, communication about menstruation is culturally constrained and girls have been instructed to keep silent about menstruation; there is a taboo that makes discussing menstruation and associated symptoms socially unacceptable (Ní Chéileachair, McGuire, & Durand, 2022).…”
Section: Introductionmentioning
confidence: 99%